RETRACTED: Therapeutic interventions impact brain function and promote post-traumatic growth in adults living with post-traumatic stress disorder: A systematic review and meta-analysis of functional magnetic resonance imaging studies - Pierce, Zachary P.; Johnson, Emily R.; Kim, Isabelle A.; Lear, Brianna E.; Mast, A. Michaela; Black, Jessica M. (Frontiers in Psychology, 2023)
The present systematic review and meta-analysis explores the impacts of cognitive processing therapy (CPT), eye movement desensitization and reprocessing (EMDR), and prolonged exposure (PE) therapy on neural activity underlying the phenomenon of post-traumatic growth for adult trauma survivors. We utilized the following databases to conduct our systematic search: Boston College Libraries, PubMed, MEDLINE, and PsycINFO. Our initial search yielded 834 studies for initial screening. We implemented seven eligibility criteria to vet articles for full-text review. Twenty-nine studies remained for full-text review after our systematic review process was completed. Studies were subjected to several levels of analysis. First, pre- and post-test post-traumatic growth inventory (PTGI) scores were collected from all studies and analyzed through a forest plot using Hedges’ g. Results indicated that all three interventions had a robust effect on PTGI scores. Next, Montreal Neurological Institute (MNI) coordinates and t-scores were collected and analyzed using an Activation Likelihood Estimation (ALE) to measure brain function. Ultimately, EMDR exhibited the largest effect on brain function, with the R thalamus (t = 4.23, p <.001) showing robust activation, followed closely by the R precuneus (t = 4.19, p <.001). T-scores and Hedges’ g values were then analyzed using Pearson correlations to determine if there were any relationships between brain function and post-traumatic growth for each modality. EMDR demonstrated the strongest correlation between increased brain function and PTGI scores (r = .910, p <.001). Lastly, all studies were subjected to a bubble plot and Egger’s test to assess risk of publication bias across the review sample. Qualitative review of the bubble plot indicated no obvious traces of publication bias, which was corroborated by the results of the Egger’s test (p = .127).